PENGARUH TINGKAT BONUS SERTIFIKAT BANK INDONESIA SYARIAH DAN TINGKAT INFLASI TERHADAP PEMBIAYAAN BANK SYARIAH DI INDONESIA - Rahmat Dahlan (Faculty of Economic and Business, 2014)
This research is to analyze to effect of Islamic bank Indonesia’s certificate bonus rate and inflation rate to Islamic bank’s financing in Indonesia. The method analysis that used in this research is multiple regressions. The dependent variable is Islamic bank’s financing, and the independent variable are SBIS’s bonus rate and inflation rate. The result shown that there is a negative effect between Islamic bank Indonesia certificate bonus rate to Islamic bank’s financing in Indonesia. But there is no effect between inflation rate and Islamic bank’s financing in Indonesia. These results indicate that the higher the level of bonus certificates Indonesia sharia banks, Islamic banks will then have a tendency to reduce the distribution of fundingDOI: 10.15408/etk.v13i2.1881